Digital Communication at the Time of COVID-19: Relieve the Refugees' Psychosocial Burden and Protect Their Wellbeing. (2nd August 2021) - Mancini, Tiziana; Imperato, Chiara; Vesco, Silvia; Rossi, Michele
Abstract: The study aims to evaluate the usefulness and effectiveness of digital communication tools implemented by an Italian NGO during the coronavirus disease 2019 (COVID-19) emergency period, considering their relations with perception of health-related risk, sense of belonging to host community, psychological distress, and wellbeing of the refugees taken in charge by the association. The study was conducted through an anonymous questionnaire proposed to a group of 102 refugees. The results confirmed that by increasing the sense of belonging to the Italian community, the time refugees spent on digital communication negatively associated with their psychological distress and positively associated with their wellbeing. Refugees' access to digital communication also increased their health-related risk perception that in turn raised their psychological distress. It specifically occurred when digital communication has been perceived as less affordable, i.e. as less clear, easy and reassuring. The results will be used to improve digital communication for health, educational, and proximity services dedicated to refugees.